Review Of Islamic Law and Human Rights On Lesbian, Gay, Bisexsual, and Transgender - Annida Fitri; Nina Sri Savarina Ulfah; Anik Priamita Lutfiana; Desy Noor Hidayah; Nazwa Syifa (Sharia Journal and Education Center Publishing, 2024)
Abstract Currently, the phenomenon of lesbian, gay, bisexual, and transgender (LGBT) has become a widely discussed issue in Indonesian society. Phenomenon has become a much-discussed issue among Indonesian society with the rampant promotion or advertisement of LGBT people on social media. The discussion of LGBT invites pros and cons in society, including academics. There are those who think that LGBT is a deviant behavior from the normal human condition, so there needs to be a ban through positive law. But on the contrary, there are also those who think that LGBT is innate since humans are born, so LGBT behavior should be accommodated through positive law as well. Islamic teachings consider that LGBT behavior is considered a fahisyah or something bad, vile, and hated, based on the Qur’an and the saheeh hadiths that support it. Keywords: Human Rights, LGBT, and Islamic Law. Keywords: Human Rights, LGBT, and Islamic Law. Abstrak Pada saat ini fenomena lesbian, gay, biseksual, dan transgender (LGBT) menjadi isu yang banyak diperbincangkan di tengah masyarakat Indonesia dengan maraknya promosi atau iklan kaum LGBT di media sosial. Pembahasan mengenai LGBT mengundang pro dan kontra di dalam tatanan masyarakat, salah satunya akademisi. Ada yang beranggapan bahwa LGBT merupakan perilaku menyimpang dari keadaan normal manusia, sehingga perlu ada pelarangan melalui hukum positif. Namun sebaliknya juga ada yang beranggapan bahwa LGBT merupakan bawaan sejak manusia dilahirkan, sehingga perilaku LGBT sudah selayaknya diakomodasi melalui hukum positif pula. Ajaran Islam menganggap bahwa perilaku LGBT dianggap sebagai sebuah fahisyah atau sesuatu yang buruk, keji, dan dibenci, berdasarkan Al Qur’an beserta hadits-hadits shahih yang mendukungnya Kata Kunci: HAM, LGBT, Hukum Islam.